Myosteatosis as a Shared Biomarker for Sarcopenia and Cachexia Using MRI and Ultrasound - Lortie, Jevin; Rush, Benjamin; Osterbauer, Katie; Colgan, T. J.; Tamada, Daiki; Garlapati, Sujay; Campbell, Toby C.; Traynor, Anne; Leal, Ticiana; Patel, Viharkumar; Helgager, Jeffrey J.; Lee, Kenneth; et al. (Frontiers in Rehabilitation Sciences, 2022)
Purpose: To establish bedside biomarkers of myosteatosis for sarcopenia and cachexia. We compared ultrasound biomarkers against MRI-based percent fat, histology, and CT-based muscle density among healthy adults and adults undergoing treatment for lung cancer. Methods: We compared ultrasound and MRI myosteatosis measures among young healthy, older healthy, and older adults with non-small cell lung cancer undergoing systemic treatment, all without significant medical concerns, in a cross-sectional pilot study. We assessed rectus femoris ultrasound-based echo intensity (EI), shear wave-based elasticity, and MRI-based chemical shift-encoded proton density fat-fraction (PDFF) for each participant. We also assessed BMI, rectus femoris thickness and cross-sectional area. Biopsies were taken from the rectus femoris of all older adults (n=20) and we analyzed chest CT scans for older adults undergoing treatment (n=10). We determined associations between muscle assessments and BMI, and compared these assessments between groups. Results: A total of 10 young healthy adults, 10 older healthy adults, and 10 older adults undergoing treatment were recruited. PDFF was lower in young adults than in older healthy adults and older adults undergoing treatment (0.3% vs 2.8% vs 2.9%, respectively, p=0.01). Young adults also had significantly lower EI than older healthy adults, but not older adults undergoing treatment (48.6 vs 81.8 vs 75.4, p=0.02). When comparing associations between measures, PDFF was highly associated with EI (ρ=0.75, p<0.01) and moderately negatively associated with elasticity (ρ=-0.49, p<0.01) but not BMI, whole leg cross-sectional area, or rectus femoris cross-sectional area. Among participants with CT scans, paraspinal muscle density was significantly associated with PDFF (ρ=-0.70, p=0.023). Histological markers of inflammation or degradation did not differ between older adult groups. Conclusion: PDFF was sensitive to myosteatosis between young adults and both older adult groups. EI was less sensitive to myosteatosis between groups, yet EI was highly associated with PDFF unlike BMI, which is typically used in cachexia diagnosis. Our results suggest that ultrasound measures could serve to determine myosteatosis at the bedside and are more useful diagnostically than traditional weight assessments like BMI. These results show promise of using EI, elasticity, and PDFF proxies of myosteatosis as diagnostic and therapeutic biomarkers of sarcopenia and cachexia.